THE SOCIO-CULTURAL AND SPIRITUAL ESSENCE OF ENTREPRENEURIAL ACTIVITY (Scientific journal of the Fergana State University, 2023)
The article analyzes the concept and essence of entrepreneurial activity from its socio-cultural and spiritual point of view. The author took a creative approach to the scientific research of foreign researchers and scientists, who helped to understand the transformation of entrepreneurial activity, relations in the coverage of the problem and expressed their views